2015
DOI: 10.1016/j.cllc.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary Treatment Options for High-Risk/Medically Inoperable Early Stage NSCLC Patients

Abstract: Lung cancer is among the most common cancers worldwide, and the leading cause of cancer death in both men and women. For patients with early stage (AJCC T1-2, N0) non-small cell lung cancer the current standard of care is lobectomy with systematic lymph node evaluation. Unfortunately, medical comorbities often present in patients with lung cancer, may preclude the option of surgical resection . In such cases, a number of minimal to non-invasive treatment options have gained popularity in the treatment of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 127 publications
2
20
0
Order By: Relevance
“…Conventional fractionated radiotherapy in treating earlystage lung cancer has left its place to stereotactic ablative body radiotherapy, and SABR is the standard treatment for T1,2 tumors (in cases with no lymph node involvement) that cannot be surgically treated for medical reasons. [10] The local control rates obtained with SABR are very good and are similar to those obtained with surgery. [9,10] In the present study, only 2 cases out of 35 patients showed post-treatment failure, and the 2-year local control rate was 93.4% ( Figure 1).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Conventional fractionated radiotherapy in treating earlystage lung cancer has left its place to stereotactic ablative body radiotherapy, and SABR is the standard treatment for T1,2 tumors (in cases with no lymph node involvement) that cannot be surgically treated for medical reasons. [10] The local control rates obtained with SABR are very good and are similar to those obtained with surgery. [9,10] In the present study, only 2 cases out of 35 patients showed post-treatment failure, and the 2-year local control rate was 93.4% ( Figure 1).…”
Section: Discussionsupporting
confidence: 71%
“…[10] The local control rates obtained with SABR are very good and are similar to those obtained with surgery. [9,10] In the present study, only 2 cases out of 35 patients showed post-treatment failure, and the 2-year local control rate was 93.4% ( Figure 1). Although local control rates were high, the overall survival rate was low in the present study (2-year total survival, 45%).…”
Section: Discussionsupporting
confidence: 71%
“…SLR confers the benefit of preserved pulmonary function in patients with intrinsic lung disease or low pulmonary reserve. 2,8 Landreneau and colleagues 9 demonstrated equivalent 5-year survival for patients undergoing video-assisted thoracoscopic surgery wedge resection when compared with patients undergoing lobectomy. 9 More recently, a systematic review performed by De Zoysa and colleagues 10 similarly demonstrated equivalent survival for patients undergoing limited resection versus lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Of note, the definition of ''medically inoperable'' or ''high-risk'' patients is not well delineated. 2 The purpose of this study was to describe national treatment and disease trends for clinical stage I NSCLC over the 15-year period from 1998 to 2012 using a large national cancer database. We hypothesized that the frequency of SBRT had increased over this time frame and that the percentage of patients receiving no treatment had decreased because of alternative therapies available for ''higherrisk'' patients.…”
mentioning
confidence: 99%
“…Cure for early (stage I and II) non-small cell lung cancer (NSCLC) is best achieved with surgical resection [2]. Other treatment modalities including radiation therapy, stereotactic radiation, and radiofrequency ablation have not yet been shown to offer the same long-term survival advantage as surgery [3]. Although surgery remains the optimal treatment choice for early NSCLC, resection rates for stage I and II range from 49% to 77% [4][5][6].…”
mentioning
confidence: 99%